Labour-market conditions of the youth in the Derecske-Létavértes sub region - Szabó, Fanni (Acta Agraria Debreceniensis, 2013)
Researches of the youth have been of great interest in social studies in the past decades, since up-coming generations provide supplies for the future, they are the so-called next generation. The problem of the young being afflicted by unemployment is more and more apparent, and not only in Hungary; moreover, in smaller, underprivileged settlements it is even more on the increase. Considering conditions of the youth in the labour-market, we can gain a valuable insight in their lifes as well as their opportunities and future prospects.